Classification of forest offences: experiences and perceptions of forest enforcers in the state of Kelantan, Malaysia - Wan Zee, Wan Nur Farinie; Hassan Zaki, Pakhriazad; Ismail, Mohd Hasmadi (Forestry Department of Peninsular Malaysia, 2022)
Achieving sustainable forest management is a crucial issue in Malaysia. Non-compliance with the National Forestry Act 1984 (Act 313) is one reason for forest offences in Malaysia. This study aimed to examine the trends of forest offences in the state of Kelantan, Malaysia from 2007 to 2016. Focusing on the experiences and perceptions of forest enforcers in Kelantan, this study of exploratory nature also aimed to identify factors that contribute to forest offences and constraints of monitoring forest offences. For this study, forest enforcers from the Kelantan State Forestry Department were purposively sampled. All data were analysed using descriptive analysis, Spearman’s correlation analysis and multiple discriminant analysis. Correlation analysis was conducted to test the relationships of the occurrence of forest offences, factors that contribute to forest offences, and constraints of monitoring forest offences. None of the variable pairings in this study were found to show acceptable association strength, although some of the pairings demonstrated significant differences. The results also showed weak discrimination between the variables fitted in the function, as respective statistics reached 1. There is a relationship between predictors with a grouping variable from a significant value of less than 0.05. Overall, the significant findings of this study would benefit related agencies in the forestry sector as guidelines for forest monitoring and management. Further study in other states of Peninsular Malaysia is required to obtain more conclusive data.